ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EFEKTIVITAS ORGANISASI DI BPS KABUPATEN/KOTA SE-NUSA TENGGARA BARAT - Chairul Fatikhin Putra; Agusdin agusdin; hermanto hermanto (Master of Management, Mataram University, 2017)
This research was aimed at determining the effect and level of trend of effect offactors affecting organizational effectiveness consisting of leadership, organizationalstructure, human resource capability, and motivation on the effectiveness of organization indistrict offices of BPS in West Nusa Tenggara. This research was quantitative descriptivestudy with 128 respondents. The data were collected through close questionnaires. The datawere analyzed using logical regression analysis with SPSS 20.0. The research showed that:(1) leadership had positive but not significant effect on organizational effectiveness, (2)organizational structure had positive and significant effect on organizational effectiveness,(3) human resource capability had positive and significant effect on organizationaleffectiveness, (4) motivation had positive and significant effect on organizationaleffectiveness, (5) good organizational structure , good human resource capability, and highmotivation had the trend of effect on how good organizational effectiveness subsequentlyas 14.22, 10.47, and 9.96 times comparing to the other side. This research recommendedthat: (1) stakeholders need to improved the quality of organizational structure, humanresource capability, and motivation for better organizational effectiveness, (2) furtherresearch need to considered other independent variables in the analysis.Keywords: organizational effectiveness, leadership, organizational structure, humanresource capability, motivation